1983
DOI: 10.1111/j.1699-0463.1983.tb00063.x
|View full text |Cite
|
Sign up to set email alerts
|

DEMONSTRATION OF A RECEPTOR FOR MOUSE AND HUMAN SERUM ALBUMIN IN STREPTOCOCCUS PYOGENES

Abstract: Demonstration of a receptor for mouse and human serum albumin. Acta path. microbiol. immunol. scand. Sect. B, 91: 373-382, 1983. A new type of surface receptor for serum albumin was detected in strains of Streptococcus pyogenes (group A). This receptor. called type e. was different from albumin receptors in other streptococcal species. Only mouse and human serum albumin was bound to the receptor. The albumin-binding capacity was high: 2 x lo8 bacterial organisms bound I I pg of mouse albumin. The receptor w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The binding of HSA to streptococci was increased three-to four-fold by aggregation, as shown by gel filtration of glutaraldehyde-treated HSA. However, the inhibition by untreated HSA showed that the binding of a*HSA was mediated by sites identical with those binding untreated albumin, recently described by Widebdck et al (23). These authors found group A streptococci to interact with murine serum albumin, and to a lesser degree with HSA.…”
Section: Discussionmentioning
confidence: 53%
“…The binding of HSA to streptococci was increased three-to four-fold by aggregation, as shown by gel filtration of glutaraldehyde-treated HSA. However, the inhibition by untreated HSA showed that the binding of a*HSA was mediated by sites identical with those binding untreated albumin, recently described by Widebdck et al (23). These authors found group A streptococci to interact with murine serum albumin, and to a lesser degree with HSA.…”
Section: Discussionmentioning
confidence: 53%
“…Similar to other streptococcal species, S . zooepidemicus binds to a number of host proteins, including immunoglobulin G [ 11 ], serum albumin [ 12 ], fibronectin, collagen [ 13 ], and α-macro-globulin [ 14 ] through cell surface components. These host-parasite recognition components may function as virulence factors by acting as adhesions or antiopsonins.…”
Section: Introductionmentioning
confidence: 99%